2012
DOI: 10.18433/j3ms40
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In Vivo Hepatic Ischemia-Reperfusion Injury on the Hepatobiliary Disposition of Rhodamine 123 and its Metabolites in Isolated Perfused Rat Livers

Abstract: -Purpose.A few studies have shown that normothermic hepatic ischemia-reperfusion (IR) injury may affect the mRNA and/or protein levels of canalicular transporters P-glycoprotein (P-gp) and multidrug resistance-associated protein 2 (Mrp2). However, the effects of the injury on the functions of these canalicular transporters with respect to the biliary excretion of drugs remain largely unknown. Therefore, the purpose of this study was to investigate the effects of warm hepatic IR on the hepatobiliary disposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 28 publications
4
12
0
Order By: Relevance
“…Because fluorescein is mainly metabolized in the hepatocyte to FG through glucuronidation, conjugating to a single glucuronic acid molecule (Chahal et al, 1985), it is likely that the increased metabolism (increased k met ) reflects an increased glucuronidation of fluorescein in the diseased 160 Thorling et al liver. This result is consistent with the previous report of the increased glucuronidation in obese humans (Hanley et al, 2010) and in hepatic I/R injury (Parasrampuria et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…Because fluorescein is mainly metabolized in the hepatocyte to FG through glucuronidation, conjugating to a single glucuronic acid molecule (Chahal et al, 1985), it is likely that the increased metabolism (increased k met ) reflects an increased glucuronidation of fluorescein in the diseased 160 Thorling et al liver. This result is consistent with the previous report of the increased glucuronidation in obese humans (Hanley et al, 2010) and in hepatic I/R injury (Parasrampuria et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…This coincided with another study of hepatic I/R injury, where the bile flow rate was 30 % lower in the I/R group compared to sham (48). In addition, another study of I/R injury reported significantly decreased bile flow at 24 h, which returned to normal values at 72 h (20). It is possible that the decreased bile flow is a result of impaired microcirculation in the liver.…”
Section: Discussionsupporting
confidence: 82%
“…As a consequence, biliary excretion rate of Rh123 was significantly decreased at 4 h of reperfusion (p<0.05). A reduced biliary excretion rate as well as decreased recovery of Rh123 was previously reported in I/R injury at 24 h of reperfusion (20,48). The reduced biliary excretion rate found in our study may also be a consequence of posttranscriptional regulation or factors such as Pgp in vivo half-life (51,52).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…37 Another recent study also found a reduced uptake and clearance of perfused rhodamine 123 in the rat liver after I/R injury. 38 To our knowledge, we are the first to use intravital imaging to visualize and model the uptake and clearance of a fluorescent compound to assess liver function following I/R injury.…”
Section: Discussionmentioning
confidence: 99%